The The Correlation Between Dietary Patterns, Nutritional Status, and Body Composition with The Performance of Football Athletes - Cahyani, Febi Ananta Indah; Indah Purnama Sari; Ditia Fitri Arinda (Universitas PGRI Palembang, 2025)
Aerobic Capacity Measured by VO₂max as a Primary Indicator of Athlete Performance: Its Correlation with Body Composition and Dietary Patterns VO₂max, an essential indicator of athletic performance, is influenced by factors such as body composition and dietary patterns. However, the relationship between these factors and VO₂max in soccer athletes remains unclear. This study aims to analyze the correlation between dietary patterns, nutritional status, body composition, and VO₂max in soccer athletes in Palembang. The research utilized an analytical survey with a cross-sectional design, involving 31 male athletes aged 15–22 years selected through purposive sampling. Data collection included anthropometric measurements, Bioelectrical Impedance Analysis (BIA), and the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ). Statistical analysis was conducted using the chi-square test to evaluate the relationship between independent variables and VO₂max. The results revealed significant correlations between muscle mass, carbohydrate intake, and protein intake with VO₂max (p < 0.05). Athletes with higher muscle mass and adequate carbohydrate and protein intake were more likely to achieve better VO₂max performance. Conversely, variables such as body fat percentage, energy intake, and fat intake showed no significant correlation with VO₂max (p > 0.05). These findings highlight the importance of optimizing muscle mass and maintaining a balanced diet, particularly adequate carbohydrate and protein intake, to enhance aerobic capacity in soccer athletes. Further research with larger sample sizes and controlled designs is recommended to validate these findings.